Lamotrigine-Related Skin Rash - Jokubaitė, J.; Martinėlė, L.; Joskaudaitė, G.; Raudonis, T. (Neurologijos seminarai, 2023)
Antiepileptic drugs can cause a variety of adverse skin reactions, from mild and transient maculopapular rash to severe and life-threatening reactions such as Stevens-Johnson syndrome or even toxic epidermal necrolysis. Lamotrigine is a new-generation aromatic antiepileptic drug whose effectiveness has been observed not only in the treatment of epilepsy but also in other disorders, such as bipolar disorder. However, this medication, like older-generation antiepileptic drugs, can cause severe skin eruptions, which limits the use of this drug in clinical practice. The main risk factors for the development of lamotrigine-related skin reactions are a high initial dose of the drug, a sudden increase in the dose of the drug, combined treatment with valproic acid, a history of skin reactions associated with the use of other antiepileptic drugs, and an age under 13 years old. Neurologists and psychiatrists should strictly follow the guidelines before prescribing this agent and apply the principles of slow titration at the beginning of treatment. To prevent significant, life-threatening consequences and control adverse events as effectively as feasible, interdisciplinary collaboration with dermatovenereologists and doctors from other specialties, early diagnosis, intense symptomatic therapy, and timely treatment are essential. The purpose of this article is to review the prevalence, clinical presentation, and recommendations for the diagnosis and treatment of lamotrigine-induced adverse skin reactions.
Keywords: lamotrigine; adverse drug reactions; cutaneous reactions; antiepileptic drugs